Risk of primary biliary liver cirrhosis in patients with coeliac disease: Danish and Swedish cohort data - Sorensen, H (1999)
BACKGROUND—Several case reports, but only a few studies, have examined the coexistence of coeliac disease and primary biliary cirrhosis.  AIM—To estimate the risk of primary biliary cirrhosis in two national cohorts of patients with coeliac disease in Denmark and Sweden.  METHODS—Through record linkage all Danish patients hospitalised with coeliac disease were followed for possible occurrence of primary biliary cirrhosis from 1 January 1977 until 31 December 1992. All patients hospitalised with coeliac disease in Sweden from 1987 to 1996 were also followed in a separate analysis.  RESULTS—A total of 896 patients with coeliac disease were identified in Denmark with a median follow up period of 9.1years for a total of 8040 person-years at risk. Two cases of primary biliary cirrhosis were observed where 0.07 were expected, giving a standardised incidence ratio of 27.6 (95% confidence interval 2.9 to 133.5). A total of 7735 patients with coeliac disease were identified in Sweden with a median follow up period of 5.1 years for a total of 39 284 person-years at risk. Twenty two people with primary biliary cirrhosis were identified compared with 0.88expected, giving a standardised incidence ratio of 25.1 (95% confidence interval 15.7 to 37.9).  CONCLUSION—Patients with coeliac disease are at increased risk of having primary biliary cirrhosis.    Keywords: coeliac disease; primary biliary cirrhosis; epidemiology; risk